What Are the Benefits of AI Virtual Health Assistants? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Artificial intelligence (AI) is rapidly and profoundly reshaping the healthcare landscape. Among the most transformative innovations are AI-powered virtual h...
Keywords: Telemedicine and Digital Health; Benefits; Virtual; Health; Artificial Intelligence; Healthcare; Digital Health